Studies of Physicochemical, Microbiological and Sensory characteristics of Paneer (Indian Cottage Cheese) to check the efficacy of clove-oil nanoemulsion in enhancing its shelf-life - D Bhardwaj; Mann, B; Sharma, R; Kumar, R; Rashmi H.M; K Gandhi; Sukthija M.P.; Minaxi Sharma (Indian Journal of Dairy Science, 2024)
Paneer is a popular dairy product in India and is highly vulnerable to spoilage due to its high moisture and nutrient content. In the presented study paneer samples were treated with clove-oil nanoemulsion and its effectiveness in enhancing the shelf-life of paneer was studied by analyzing the physicochemical, microbiological and sensory characteristics of the stored samples. Paneer treated with clove-oil nanoemulsion showed the lesser significant increase (P<0.05) in extent of proteolysis and free-fatty acid content while preventing reduction in moisture and pH of treated samples in comparison to control. Microbiological analysis revealed that paneer samples treated for 15 min with clove oil nanoemulsion followed by packing in nanoemulsion treated packaging material showed reduction in Standard plate count, coliform and Yeast and mold count by 2.02, 2.43 and 1.88 log cycles respectively in comparison to untreated control paneer samples on 21st day of storage. Treated paneer samples were observed to elicit almost constant sensory scores throughout the storage period as compared to control which showed significant reduction (P<0.05) in sensory scores throughout the storage period.